Direct Gold-Catalyzed Regioselective Tetrafunctionalization of Nonactivated Alkynes - Wei, Fang; Wang, Xianghua; Peng, Shasha; Jia, Qiuhui; Jiang, Chao; Liu, Shili; Xu, Zhenghu (Synthesis, 2014)
A simple and efficient method based on gold catalysis is reported for the synthesis of halogen-functionalized pyrrolidine aminals. A new alkyne tetrafunctionalization strategy is proposed for the first time.
Keywords: tetrafunctionalization; alkynes; gold; catalysis; pyrroles